The Analysis of Student Teacher’s Lesson Plan in Implementing Student-Centered Learning Approach - Sumarniningsih, Sumarniningsih; Ramadhan, Rizki; Dwi Iswati, Henny; Asning Tias, Silfia; Chakim, Nur (Jayapangus Press, 2025)
One of the key instruments to support teaching and learning process is the lesson plan. Developing a lesson plan can help teachers facilitate the lesson, set the teaching goals and learning objectives, organize and manage the teaching and learning activities, and set the means to accomplish them. This research aims to investigate the aspect taken in lesson plan in implementing student-centered learning approach and how it is implemented in the classroom. A qualitative method was employed to analyze as many as 6 lesson plans developed by 6 PPG Unesa student teachers. The data were gathered from document analysis. The documents were lesson plans and teaching videos. The theories were composed from several frameworks that were utilized to measure the aspects of student-centered learning approach in lesson plan such as active learning instruction, teacher as facilitator, differentiated instruction, and formative assessment. In conclusion, the implementation of this approach was still facing some challenges. These include a limited range of instructional materials, language proficiency issues, the use of repetitive activities, and a lack of feedback, which can impede the efficacy of a student-centered approach.